Stress-transfer from polymer substrates to monolayer and few-layer graphenes. Issue 12 (21st November 2019) - Androulidakis, Ch.; Sourlantzis, D.; Koukaras, E. N.; Manikas, A. C.; Galiotis, C.
Abstract : In the present study, the stress transfer mechanism in graphene–polymer systems under tension is examined experimentally using the technique of laser Raman microscopy. Abstract : In the present study, the stress transfer mechanism in graphene–polymer systems under tension is examined experimentally using the technique of laser Raman microscopy. We discuss in detail the effect of graphene edge geometry, lateral size and thickness which need to be taken under consideration when using graphene as a protective layer. The systems examined were composed of graphene flakes with a large length (over ∼50 microns) and a thickness of one to three layers simply deposited onto PMMA substrates which were then loaded to a tension of ∼1.60% strain. The stress transfer profiles were found to be linear while the results show that large lateral sizes of over twenty microns are needed in order to provide effective reinforcement at levels of strain higher than 1%. Moreover, the stress built up has been found to be quite sensitive to both edge shape and geometry of the loaded flakes. Finally, the transfer lengths were found to increase with the increase of graphene layers. The outcomes of the present study provide crucial insight into the issue of stress transfer from polymers to graphene nano-inclusions as a function of edge geometry, lateral size and thickness in a number of applications.